Salmonella enteritidis in the eggs of Japanese quails (coturnix coturnix Japonica - Temminck & Schlegel, 1849) fed diets with different calcium and phosphorus levels - Eri, Katayama; Donato, T. C. [UNESP]; de Silva, A. P. [UNESP]; Mazola, R. P.; Garcia, Edivaldo Antonio [UNESP]; Okamoto, Adriano Sakai [UNESP]; AndreattiFilho, R. L. [UNESP] (FapUNIFESP (SciELO), 2013)
Several studies point out that eggs are the main cause of human salmonellosis, particularly when poorly processed or eaten raw. In addition of causing public health problems, the presence of Salmonella hinders international food trade, and therefore, it is a health barrier. There are several predisposing factors for the contamination of internal egg content by Salmonella spp, including eggshell quality, which is related to dietary calcium (Ca) and phosphorus (P) levels. In this study, eggs from Japanese quails fed diets containing two different Ca (2.0 or 3.5%) or P (0.25 or 0.45%) levels were evaluated. Three production phases were used in the experiment: starter, intermediate, and final. The presence of Salmonella Enteriditis in the eggshell and internal content in in the periods of 0, 24, 96, and 168 hours after the experimental contamination of the eggs by immersion in broth containing Salmonella Enteriditis. The bacterium was detected in decreasing numbers in the eggshell of eggs from all treatments and during all storage periods. No significant bacterial numbers were found in the internal egg content in none of the treatments during none of the production phases. Therefore, the evaluated Ca and P levels in the diet of Japanese quails did not result in higher or lower public health risk relative to the presence of Salmonella Enteritidis in the internal egg content.